Fashion figures : how missy the mathlete made the cut (2017)
The inspiration for this story came to me when researching a blog, I discovered that girls as young as third and fourth graders were opting out of STEM (Science, Technology, Engineering, and Math) tracks. That means that at nine years old, girls are closing career doors they may not even know exist yet. The choices they make have nothing to do with skills or ability but rather are driven by unconsious biases and false assumptions. As we hear more about the dearth of women in tech fields, it’s easy to connect the dots. We cannot wait to address this in college or even in high school, as foundational skills for STEM need to be built much earlier. This is a problem that has to be solved in elementary and middle school. Girls need to be encouraged to engage in STEM subjects as early as possible, not just to fill the pipeline but also to drive inclusion and diversity. This book is written for middle-schoolers facing the pressures of growing up in a hyperconnected, technology-driven universe where traditional social, educational and personal pressures also persist. This book shows how one girl stuggles with social pressures, varied academic interests and a deep desire to help her friends, family and the world she lives in to be better. She embraces her inner geek, her artistic flair and her heart’s true desires to find her way. I hope it inspires more girls to pursue their interests in math AND the arts and to grow their talents to help make our world a better and brighter place for all.